Contemporary jurisprudential analysis of modern transportation's impact on rulings concerning unaccompanied female travel - Hasin, Abdul Wasi; Zaroum, AbdulHamid Mohamed Ali (Islamic Book Trust Kuala Lumpur (IBT) & Contemporary Fiqh Research Unit (CFRU), IIUM, 2025)
Abstract This study explores the impact of modern means of transportation on women traveling without a mahram in contemporary Islamic societies. The research highlights the opinions of Islamic scholars in this regard. The study also sheds light on the point of view of Islamic societies towards women’s travel using modern means of transport and provides a strong look at the views of Islamic societies on the issue of women’s travel without a mahram, especially the extent of the availability of modern means of transport. Can these developments affect the redefinition of the need for what is Mahram? Given the keenness of Islamic law to bring benefits, ward off harm, preserve honor and lineage, and block pretexts; The research discusses the challenges and potential benefits of these methods at the individual and societal levels? The research discusses the challenges and potential benefits of these changes at the individual and societal levels. The study aims to provide insights into the religious, cultural, and technological interaction that shapes the context of the dialogue around women’s independence in travel. It seeks to shed light on the cultural and religious context surrounding this growing controversy in contemporary Islamic societies.